Long-term Evolution of Maternal and Child Health Indicators in Indonesia: Evidence from 28 Years of National Health Data - Ayu Rahayu; Abar, Nur Rahmah Yunita (Jurusan Matematika FMIPA UNM, 2025)
Indonesia has undergone significant healthcare system transformations over the past three decades, including the implementation of universal health coverage in 2014. However, comprehensive long-term analyses of maternal and child health (MCH) trends spanning nearly three decades remain limited. This study examines the evolution of key MCH indicators in Indonesia from 1995 to 2023 to assess progress, identify patterns, and inform future policy directions. We conducted a longitudinal trend analysis using data from the Indonesian National Health Survey (Riset Kesehatan Dasar/Riskesdas) covering the period from 1995 to 2023. Nine key indicators were analyzed: prevalence of health complaints, skilled birth attendance, childhood immunization coverage (BCG, DPT, polio, measles), and breastfeeding practices. Statistical methods included linear trend analysis, Bayesian changepoint detection, correlation analysis, and segmented regression to assess policy impacts. Healthcare utilization patterns, including outpatient care, inpatient care, self-medication, and traditional medicine use, were examined as contextual indicators. Substantial improvements were observed across most MCH indicators over the 28 years. Skilled birth attendance showed the most dramatic progress, increasing from 46.1% (1995) to 95.7% (2023), representing an annual improvement rate of 2.55%. Childhood immunization coverage achieved high levels (>85%) for most vaccines by the 2000s, though measles vaccination remained variable (54-80% range). Breastfeeding patterns showed a structural break in 2015 due to methodological changes, which complicated trend interpretation. Healthcare utilization evolved significantly, with outpatient care increasing from 20% to >50% before declining to 35% by 2023, while self-medication practices rose substantially to 80%. Correlation analysis revealed alignment between health needs and service utilization (r = 0.48 for outpatient care). Changepoint analysis identified accelerated improvements around 2000-2005 and 2014-2015, coinciding with healthcare decentralization and universal coverage implementation respectively. Indonesia achieved remarkable progress in maternal and child health over 28 years, with skilled birth attendance approaching universal coverage and immunization programs maintaining high performance. The implementation of universal health coverage in 2014 coincided with continued improvements, though some recent declines in vaccination coverage warrant attention. The evolution from traditional medicine to modern healthcare services, alongside increasing self-medication practices, reflects maturing health systems requiring adaptive policy responses. Indonesia's experience demonstrates that sustained MCH improvements are achievable in large middle-income countries through systematic health system strengthening, though maintaining momentum requires continuous adaptation to emerging challenges. These findings provide valuable insights for other countries pursuing similar health system transformation goals.